Theological Ethics and The Naturalistic Fallacy - Crossley, John P. (Journal of religious ethics, 1978)
Theological ethics is vulnerable to the charge made by some philosophical ethicists that it frequently commits the "naturalistic fallacy," i.e., that it fallaciously derives duties and obligations from purely descriptive theological premises. Some theological ethicists, acceding to the charge, have contented themselves with an examination of how theological ethics might "influence" or "enrich" ethical propositions based on non-theological foundations. This essay analyzes the current scene in theological ethics and argues that the "naturalistic fallacy" is not the real danger. The real danger is the failure of theological ethics to work out both its theological and ethical propositions in close relationship to human experience and to each other.